2020
DOI: 10.1038/s41598-020-69869-0
|View full text |Cite|
|
Sign up to set email alerts
|

Setting a baseline for global urban virome surveillance in sewage

Abstract: The rapid development of megacities, and their growing connectedness across the world is becoming a distinct driver for emerging disease outbreaks. Early detection of unusual disease emergence and spread should therefore include such cities as part of risk-based surveillance. A catch-all metagenomic sequencing approach of urban sewage could potentially provide an unbiased insight into the dynamics of viral pathogens circulating in a community irrespective of access to care, a potential which already has been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 62 publications
3
34
0
3
Order By: Relevance
“…NGS analysis can unravel the diversity of viruses within a complex sample such as wastewater, particularly by using unbiased sequencing of the sewage virome ( 43 ). Nevertheless, the detection of variants of a virus in a single sample can be challenging because of the relatively low number of reads obtained for each virus.…”
Section: Discussionmentioning
confidence: 99%
“…NGS analysis can unravel the diversity of viruses within a complex sample such as wastewater, particularly by using unbiased sequencing of the sewage virome ( 43 ). Nevertheless, the detection of variants of a virus in a single sample can be challenging because of the relatively low number of reads obtained for each virus.…”
Section: Discussionmentioning
confidence: 99%
“…In depth NGS analysis could help to unravel the diversity of viruses within a complex sample such as wastewater, particularly unbiased sequencing of the sewage virome can give a good picture of the general viral diversity contained in a sample 36 . Nevertheless, the detection of variants of a particular virus in a single sample can be difficult due to the relative low number of reads obtained for each virus type.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we proposed methodological approaches that aimed to eliminate as much as possible bacteria, shellfish tissues, or free DNA or RNA (Strubbia et al, 2020), to focus on RNA viruses. This likely explains the low amount of DNA and phages viruses reads in our study unlike agnostic metagenomic studies where these viruses constituted the largest viral fraction (Bačnik et al, 2020;Nieuwenhuijse et al, 2020). We also performed technical triplicates of cDNA synthesis and libraries as we observed that it increases the odds to recover sequences from viruses present at low concentrations (Strubbia et al, 2020).…”
Section: Discussionmentioning
confidence: 91%